Book Reviews / Rezensionen - Berksoy Bilgin; Eckhard Hein; Hermann Rauchenschwandtner; Kai Eicker-Wolf (Intervention. European Journal of Economics and Economic Policies, 2008)
Books reviewed: Becker, Joachim/Weissenbacher, Rudy (2007): Dollarization, Euroization and Financial Instability. Central and Eastern European Countries between Stagnation and Financial Crisis?, Marburg Arestis, Philip/Sawyer, Malcolm (eds.) (2006): A Handbook of Alternative Monetary Economics Schürz, Martin/Weber, Beat (2008): Das Wissen vom Geld. Auf dem Weg zum Finanzbildungsbürgertum, Graz Görgens, Hartmut (2008): Sind die Löhne in Deutschland zu hoch? Zahlen, Fakten, Argumente, 2. überarbeitete Auflage, Marburg Bosch, Gerhard/Weinkopf, Claudia (Hg.) (2007): Arbeiten für wenig Geld. Niedriglohnbeschäftigung in Deutschland, Frankfurt
Keywords: 330